Low-dose hydrocortisone replacement is associated with improved arterial stiffness index and blood pressure dynamics in severely adrenocorticotrophin-deficient hypopituitary male patients. Issue 6 (June 2016) - Behan, Lucy-Ann; Carmody, David; Rogers, Bairbre; Hannon, Mark J; Davenport, Colin; Tormey, William; Smith, Diarmuid; Thompson, Christopher J; Stanton, Alice; Agha, Amar
Abstract : Objective: Increased cardiovascular and cerebrovascular morbidity and mortality in hypopituitary subjects may be linked to inappropriate glucocorticoid exposure; however, the pathophysiology remains unclear. We aimed to examine the effect of three commonly prescribed hydrocortisone (HC) regimens on vascular risk factors. Design: An open crossover study randomising ten hypopituitary men with severe adrenocorticotrophic hormone deficiency to three HC dose regimens: dose A (20mg mane and 10mg tarde ), dose B (10mg mane and 10mg tarde ) and dose C (10mg mane and 5mg tarde ). Methods: Following 6 weeks on each regimen, participants underwent 24-h serum cortisol sampling, 24-h ambulatory blood pressure (BP) measurements, calculation of the Ambulatory Arterial Stiffness Index (AASI), oral glucose tolerance testing and fasting serum osteoprotegerin (OPG) sampling. Results: There were no differences in 24-h BP between dose regimens and controls; however, low-dose HC replacement (dose C) was associated with the lowest AASI, indicating a less stiff arterial tree ( P <0.05) compared with the other dose regimens. Loss of the physiologic nocturnal BP dip was more common in higher HC replacement regimens, although only significant for dose B compared with dose C ( P =0.03). Twenty per cent of patients had abnormal glucose tolerance, but this was unrelated to dose regimen. OPG correlated strongly with 24-h BP in those on dose A only ( r =0.65, P =0.04). Conclusion: Currently prescribed HC replacement doses do not result in significant differences in absolute BP levels or improvements in insulin sensitivity. However, lower HC doses may result in lower arterial stiffness and a more physiological nocturnal BP dip. Long-term studies are required to confirm these findings and evaluate their impact on vascular morbidity in this patient group.